PERAN SDM TERHADAP KINERJA PEGAWAI MELALUI KECERDASAN EMOSIONAL PADA BIRO KEMENPAREKRAF INDONESIA - Holilah, Siti (Universitas Prof. Dr. Moestopo (Beragama), 2025)
This study aims to examine the role of human resources in employee performance with emotional intelligence as a mediating variable in the Bureau of the Ministry of Tourism and Creative Economy of Indonesia. A quantitative approach with an explanatory research design was employed, using a census method involving bureau employees. Data were collected through structured questionnaires and analyzed using mediation regression analysis. The findings reveal that human resource quality has a positive and significant effect on employee performance. Human resources also significantly influence emotional intelligence, while emotional intelligence demonstrates a positive effect on employee performance. Mediation analysis confirms that emotional intelligence partially mediates the relationship between human resources and employee performance. These results indicate that employee performance improvement is not solely driven by technical competence and work attitudes, but also by the ability to manage emotions effectively in the workplace. This study highlights the importance of integrating emotional intelligence development into human resource management strategies to enhance performance effectiveness within public sector organizations.